Antiglycation activity of lipophilized epigallocatechin gallate (EGCG) derivatives. (1st January 2016) - Wang, Mingfu; Zhang, Xinchen; Zhong, Ying Joy; Perera, Nishani; Shahidi, Fereidoon
Highlights: EGCG's in vitro antiglycation activity is preserved after lipophilization. Fatty acid chain length affects free radical and carbonyl scavenging activity. Lipophilized EGCG derivatives are promising in vivo AGE-inhibitors. Abstract: Lipophilized EGCG derivatives were synthesized by esterification of EGCG with aliphatic fatty acids and demonstrated to possess many advantages, such as higher lipophilicity and apparent health benefits over the parent EGCG. This study used a total of seven lipophilized EGCG derivatives with fatty acids of different chain lengths attached and examined the impact of lipophilization on EGCG's antiglycation activity in vitro . The length of fatty acid chain was found to be an important factor, which positively correlated with ABTS radical scavenging capacity but long chain bulky substitutes prevented methylglyoxal (MGO) trapping. Except docosahexaenoic acid (DHA), lipophilization generally showed no interference with EGCG's in vitro inhibitory activity of advanced glycation endproducts (AGEs) formation. Therefore, the lipophilized EGCG derivatives are promising candidates worthy of further exploration for preventing AGEs accumulation in vivo and hence treating AGEs-associated diseases.